Effects of acute caffeine ingestion on futsal performance in sub-elite players - López Samanes, Álvaro (2021)
Purpose To date, no previous investigation has studied the effect of acute caffeine ingestion on futsal performance during futsal-specific testing and during a simulated match. Therefore, the aim of this investigation was to establish the effects of acute caffeine intake on futsal-specific tests and match-play running performance in male futsal players. Methods Sixteen high-performance futsal players participated in a randomized, crossover, placebo-controlled and double-blind experiment. Each player completed two identical trials after ingesting either caffeine (3 mg/kg) or a placebo (cellulose). The trials consisted of a battery of futsal-specific tests (countermovement jump, 20-m sprint test, and a futsal kicking velocity and accuracy test) followed by a simulated futsal match (2 halves of 7.5 min). During the match, players’ running performance was assessed with local positioning system devices. Results In comparison to the placebo, caffeine ingestion increased jump height by 2.8% (p = 0.048; ES = 0.29) and reduced the time to complete the 20-m sprint test by -2.2% (p = 0.044; ES = − 0.54). Additionally, acute caffeine intake improved the distance covered at above 14.4 km/h by 19.6% (p = 0.021; ES = 0.58), the number of body impacts by 8.1% (p = 0.040; ES = 0.27) and the number of accelerations/decelerations by 4.2% (p = 0.044; ES = 0.57) during the simulated futsal match. However, no differences were reported in ball velocity or shooting accuracy in the futsal kicking test. There were no differences in the prevalence of side effects reported in the hours after the ingestion of the treatments. Conclusion Three mg/kg of caffeine enhanced several physical variables associated with futsal such as jump and sprint performance, and improved high-speed running and accelerations/decelerations during a simulated futsal match. Caffeine supplementation with a moderate dose can be considered as an effective ergogenic aid for futsal performance with low prevalence of side effects.